ATR-FTIR study of the hygroscopicity of sodium nitrate aerosols - Gao Yuyi; Zhang Yunhong (E3S Web of Conferences)
Nitrate aerosol is a significant component of atmospheric aerosols, and its impact on the atmospheric environment, climate, and human health has garnered increasing attention from the scientific community. The rise in nitrogen oxide emissions has led to a rapid increase in atmospheric nitrate levels. Nitrate aerosols can influence climate through direct and indirect effects, contributing to urban haze formation and acid rain production. The hygroscopicity of atmospheric aerosols plays a crucial role in determining particle size, morphology, chemical composition, heterogeneous reactivity, and cloud condensation nuclei activity. Therefore, the research on the hygroscopicity of atmospheric aerosols is helpful to reveal the complex physical and chemical processes of atmospheric aerosols, provide the formation and evolution mechanism of atmospheric haze pollution, and realize the precise prevention and control of haze pollution. The attenuated total reflectance Fourier transform infrared spectroscopy (ATR-FTIR) technology is highly sensitive and nondestructive, allowing aerosol samples to be analyzed in their original state. It enables continuous, dynamic, real-time, and online monitoring of aerosols. In this study, ATR-FTIR was employed to determine that the weathering point of nitrate aerosol is 56.8% RH and the deliquescence point is 83.5% RH. The heterogeneous nucleation rate (Jhet) increased by approximately two orders of magnitude, from 7.29 × 108 m−2s−1 to 4.88 × 1010 m−2s−1, as humidity decreased. Conversely, the deliquescence rate (J) increased by about three orders of magnitude, from 7.5 × 10−3 s−1 to 3.56 s−1, as humidity increased. Furthermore, the study compared the effects of different substrates on the heterogeneous nucleation rate and deliquescence rate, which aids in the development of more comprehensive atmospheric models.